THE EFFECT OF INFORMATION TECHNOLOGY, ORGANIZATIONAL COMMITMENT, INTERNAL CONTROL AND GOOD CORPORATE GOVERNANCE PRINCIPLES ON ORGANIZATIONAL PERFORMANCE - Sahusilawane, Wildoms (International Journal of Social Science and Business, 2020)
The aim of this research is to critically evaluate information technology, organizational commitment, internal control, and the implementation of the principles of good corporate governance and describe how the key elements of these constructs contribute to the performance of PT. Bank Maluku. To this end, a sample of 40 employees at PT Bank Maluku is identified and examined using non probability purposive sampling. Primary data results from questionnaires complemented by interviews for data collection. The data is analyzed using correlation analysis and multiple regression that includes descriptive statistics and reliability and validity test of the research instrument. The research study proceeds to classical assumption test including multicollinearity test, hypothesis testing within the model and discussion on result. The results of the analysis based on t test greatly vary. Information technology is found negative and non significant in organizational performance. Both organizational commitment and internal control, to the contrary, pose positive yet non significant effect on organizational performance, while the implementation of the principles of good corporate governance poses positive relationship and are statistically significant in organizational performance